2010
DOI: 10.1002/clen.201000145
|View full text |Cite|
|
Sign up to set email alerts
|

Trace Elements in Sediments and Mussels – Spatial Distribution, Chemical Partitioning, and Risk Assessment

Abstract: Sediment samples were collected from 30 different locations in Abu Qir Bay (Mediterranean Sea), East Alexandria, Egypt and analyzed for trace elements. The highest concentrations of most of the elements were observed in the nearshore stations in the vicinity of the major anthropogenic activities as industrial settlements, waste-water discharges, and agricultural drainage. In addition, mussel samples of Mactra corallina and Tapes decussata were collected corresponding to the sediment samples. Concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…One of the most important methods developed in this area belongs to Long and MacDonald 49 and MacDonald et al 50 , who suggest “consensus-based” SQGs for assessing the environmental effects of metals. Consensus-based SQGs are determined as the geometric mean of different SQGs 51 , including those obtained using US-EPA and other similar guidelines 52 . Consensus-based SQGs contain two effect values, namely the threshold effect concentration (TEC) and the probable effect concentration (PEC).…”
Section: Resultsmentioning
confidence: 99%
“…One of the most important methods developed in this area belongs to Long and MacDonald 49 and MacDonald et al 50 , who suggest “consensus-based” SQGs for assessing the environmental effects of metals. Consensus-based SQGs are determined as the geometric mean of different SQGs 51 , including those obtained using US-EPA and other similar guidelines 52 . Consensus-based SQGs contain two effect values, namely the threshold effect concentration (TEC) and the probable effect concentration (PEC).…”
Section: Resultsmentioning
confidence: 99%
“…As with the increased legislation on soil contamination by heavy metals, there is an increased demand for methods of risk assessment [23]. Some studies have proposed sequential extraction methods for risk assessment, especially for the potential solubility and mobility of metals in metal contaminated soils [24,25]. In European countries, the use of batch experiments as methods of risk assessment in metal contaminated soils is increasing [23].…”
Section: Introductionmentioning
confidence: 99%
“…Giustui et al [19] confirmed that marine organisms" tissues in polluted area could accumulate heavy metals. Bivalves could serve as pollution bio-indicators for metals in Egyptian water [20] . Fe is more concentrated in date mussels" tissues followed by Zn> Cu >Cd >Pb> Cr> Co and Ni in the current study.…”
Section: Discussionmentioning
confidence: 99%